2019
DOI: 10.3390/nano9020145
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of Lambda-Cyhalothrin Nanosuspension by One-Step Melt Emulsification Technique

Abstract: Recent years have witnessed significant progress in nanotechnology and pesticide research in pest control and crop protection. There are more motivations to develop nanoformulations that are less harmful to environment than conventional formulations. The use of nanosuspension has been proposed as a novel formulation to process poorly soluble pesticides. In this study, the lambda-cyhalothrin nanosuspension (LCNS) was prepared in a melt emulsification method. The prepared nanosuspension had a mean particle size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Pesticides are important agrochemicals that are widely used to control pests, preventing crop loss caused by major diseases and pests and increases crop yield [1,2,3]. Most pesticides need to be formulated using suitable formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are important agrochemicals that are widely used to control pests, preventing crop loss caused by major diseases and pests and increases crop yield [1,2,3]. Most pesticides need to be formulated using suitable formulations.…”
Section: Introductionmentioning
confidence: 99%
“…The PDI of nanocarriers with various PLGA amounts showed a narrow size distribution of approximately 0.172 to 0.212, with an observed PDI value of less than 0.300. [34] These results indicate that the nanocarriers in each group had similar properties. SEM results showed that the nanocarriers were spherical with a relatively uniform size, which corresponds to the PDI, as presented in Figure 2.…”
Section: Effect Of Plga Amountmentioning
confidence: 66%
“…Table 5 summarizes the effect of PVA concentration on the nanocarriers. An increase in PVA concentration increased the nanocarrier size and the observed PDI value of less than 0.300 [34] because increasing the concentration expanded entanglement of the polymer chains. Drug loading and %yield was not influenced by PVA concentration.…”
Section: Effect Of Pva Concentrationmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent years, surfactants have commonly been mixed to further improve their performance by taking advantage of their synergistic effects [48]. Correct surfactant content plays an important role in stabilizing nanoparticles [49,50]. In the current study we mixed the two selected surfactants that demonstrated good emulsification effects and tested their performance in different ratios (PVA: PC = 1:1, 1:2, 2:1, 1:3, and 3:1).…”
Section: Complex Surfactantsmentioning
confidence: 99%